RESULTS OF DOUBLE STARS OBSERVATIONS AT NIKOLAEV OBSERVATORY - Bodryagin, D. V.; Maigurova, N. V. (Одеські астрономічні публікації, 2016)
The results of double stars observations at Nikolayev Observatory during 2013-2014 are presented. The Washington Double Stars Catalogue (WDS) was used for observation program composing. The observation volume was obtained with usage two telescopes equipped CCD-cameras. Precise modern epoch CCD-observations allowed to make new proper motion values. The position angles and separations for 214 double stars were measured. Results are going to be submitted to WDS.